Rancang Bangun Alat Perontok Gabah Padi Berbasis Mikrokontroler ATmega 8535 - M Dicky Wandana; Hendri Hendri (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Threshing rice paddy is an important part of the rice processing process. Because the threshing and machining process used to eradicate rice grain is one of the important factors so that rice yields can be maximally obtained by farmers. Therefore, there needs to be an effort and innovation that must be made for the availability of an effective rice grain threshing machine. So that the rice grain threshing process can be carried out more efficiently, so that it can achieve more optimal yields and reduce the possibility of failing post-harvest rice yields. The DC motor in this tool uses as a cylinder drive which is used as threshing paddy rice. In order for the dc motor to rotate when it detects the presence of rice grain which is inserted in the mouth of the machine, Infra red sensors and photo diode are installed to detect the absence of rice grain. Signals that are read by Infra Red and photo diodes are sent to the ATmega 8535 as the controller. This paper presents the design of the grain threshing device using ATmega 8535. The motor parameters that are controlled the speed of the DC motor. The results of the preparation and testing showed that the rice grain threshing tool made was in accordance with the plan.